ABOUT USING INTERACTIVE METHODS IN TEACHING UZBEK LITERATURE - Mahmudova, Sevara (Journal of Higher Education and Academic Advancement, 2024)
This article discusses the use of interactive methods in teaching Uzbek literature in higher educational institutions. Modern education requires the use of many methods, such as brainstorming, discussion, problem situation, reference text, project, role-playing game, as well as encouraging students to perform practical exercises. Interactive methods are a form of dialogic learning based on mutual cooperation between student and teacher; such methods contribute to the formation of certain skills and abilities in students, create an atmosphere of cooperation in the classroom, interact and allow the teacher to be a leader. When studying fiction, it is very important to directly read and understand the work of art itself, the text